Do Economic Policy Uncertainty Have Ramifications on Inflation and Stock Market Performance? Evidence from Global Framework - Mishra Amritkant (Studies in Business and Economics)
This pragmatic study aims to comprehensively examine the underlying impact of economic policy uncertainty (EPU) on both inflation and stock market performance across fifteen major global economies, employing the robust panel Autoregressive Distributed Lag (ARDL) model. The outcome reveals that there is a long-run nexus between the EPU, inflation, and the stock market across fifteen countries. The empirical consequences further show that, in the long run, EPU has an adverse impact on inflation. Additionally, outcomes affirm that the short-run impact of economic policy uncertainty is not uniform across countries. Finally, the result further confirms the positive long-run impact of economic policy uncertainty on the stock market’s performance. The insights gleaned from this study hold valuable implications for policymakers, empowering them to devise more effective and informed policy strategies. Policymakers can effectively leverage these comprehensive findings to design well-targeted measures aimed at mitigating the adverse effects of economic policy uncertainty and fostering economic stability and growth.